PT.USAHA LANTANG SEJAHTERA JAKARTA PENGARUH SISTEM PENGENDALIAN INTERNAL PIUTANG DAN AKUNTANSI PENJUALAN KREDIT TERHADAP EFEKTIVITAS PENAGIHAN PIUTANG PADA - Zulkarnain Moeshak Zen (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2016)
Accounts receivable billing activity an important part in launching the distribution of the company's revenue was then used as working capital and the smooth turnover of the company assets on an ongoing basis. This study aims to determine, describe and explain Effect of Internal Control Systems Receivable and Cash Receipts Effectiveness Against Accounts Receivable Billing. Variables examined in this study is the Internal Control System Receivables (X1), Credit Sales Accounting (X2) as independent variables. Effectiveness Billing and Accounts Receivable (Y) as the dependent variable. The popolasi in this study are based on the amount of saturated sample method. In the event, the number of samples studied as many as 31 employees associated with the sale and collection of accounts receivable. Descriptive method that aims to investagate relationships between variables or role, through a quantitative approach and statistical tests. Data collected by melakukann observation, interviews, distributed questionnaires and literature study. Money analysis method used is the Pearson correlation coefficient public, research hypothesis will be tested using the F test and t test. Based on the results of research and discussion conducted has obtained the results of R square of 0.577 which means a very strong relationship between the three variables, and supported by the hypothesis testing of the internal control system variables receivable (X1) through the t test where t count> t table (4,219> 2,037) and a variable sales accounting (X2) t> t table (3,887 > 2,037). Thus the hypothesis test results are acceptable, so that it can be concluded that the Internal Control System Receivable and Credit Sales Accounting Contribute Effectiveness Against Accounts Receivable Billing. As well as the calculation of the variable coefficient partial Internal Control Systems results obtained Receivables 54,2%, which means that 54,2% Internal Control System contributes to the effectiveness of Billing Accounts Receivable while the rest influenced by other factors not examined. And from variable Credit Sales Accounting obtained yield was 57,7%, which means that 57,7% of credit sales accounting contribute to the effectiveness of the collection of accounts receivable and the rest influenced by other factors not examined .